2017
DOI: 10.1136/archdischild-2017-312744
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for neonatal encephalopathy: an unmatched case-control study

Abstract: ObjectiveNeonatal encephalopathy (NE) is the third leading cause of child mortality. Preclinical studies suggest infection and inflammation can sensitise or precondition the newborn brain to injury. This study examined perinatal risks factor for NE in Uganda.DesignUnmatched case–control study.SettingMulago National Referral Hospital, Kampala, Uganda.Methods210 term infants with NE and 409 unaffected term infants as controls were recruited over 13 months. Data were collected on preconception, antepartum and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 32 publications
4
64
2
Order By: Relevance
“…In line with findings from another Ugandan study [24], we observed that FHR was not monitored in the second stage of labor. One of the reasons could be that although the WHO guidelines recommend listening to FHR every 5 min during the second stage of labor, the Ugandan clinical guidelines do not give guidance regarding FHRM during this stage [6,17].…”
Section: Discussionsupporting
confidence: 91%
“…In line with findings from another Ugandan study [24], we observed that FHR was not monitored in the second stage of labor. One of the reasons could be that although the WHO guidelines recommend listening to FHR every 5 min during the second stage of labor, the Ugandan clinical guidelines do not give guidance regarding FHRM during this stage [6,17].…”
Section: Discussionsupporting
confidence: 91%
“…Fetal inflammation (funisitis) and early neonatal bacteraemia have been shown to be independent risk factors for encephalopathy (Tann et al . ). Late onset bacteraemia (due to factors such as long‐term indwelling catheters) in preterm infants during postnatal weeks 2–4 is associated with a greater risk of neurocognitive limitations at age 10 years (Bright et al .…”
Section: The Global Burden Of Hypoxic–ischaemic Brain Injurymentioning
confidence: 97%
“…A plausible hypothesis might be that the inflammatory activation in the absence of marked temperature changes lowers the threshold to cellular injury from an HI insult, without leading to neuronal necrosis, and thereby maintaining susceptibility to hypothermic rescue. The increased rate of infection (6–13%) among HIE neonates, compared to 0.5–1% in the general term-born neonatal population, supports the theory of elevated susceptibility to HI [39, 40]. HT reduces mortality and severe neurological morbidity in asphyxiated neonates, even though the investigated cohorts include infants with severe encephalopathy of HI origin both with and without infectious pre-exposure [1, 41].…”
Section: Discussionmentioning
confidence: 81%